Asymmetric PMP hollow fiber oxygenation membrane as well as preparation method and application thereof

By regulating the structure of the PMP oxygenated film, including a dense outer surface, appropriate porosity and separation ratio, the problem of insufficient oxygenation performance of the existing oxygenated film is solved, efficient oxygen and carbon dioxide exchange is achieved, close to the performance of the human lungs, and prolonging the service life.

CN120079256APending Publication Date: 2025-06-03HANGZHOU FAIR INNOVATIVE MATERIALS CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510253209.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-05
Publication Date
2025-06-03

AI Technical Summary

Technical Problem

The oxygenation performance of the existing PMP hollow fiber oxygenation film is still far from that of the human lungs, and it is necessary to further improve the oxygenation performance.

Method used

By regulating the structure of the oxygenated film, it has a suitable oxygen flux and a high separation ratio between carbon dioxide and oxygen, and a rapid exchange of oxygen and carbon dioxide is achieved. Specific measures include: the outer surface is dense, the initial bubble point of hydrofluoroether is not less than 2MPa, the porosity is 40%-70%, the oxygen flux is 1ml/(cm2×min×bar)-2.5ml/(cm2×min×bar), and the separation ratio of carbon dioxide and oxygen is not less than 1.8.

Benefits of technology

It significantly improves the oxygenation performance of the oxygenation film, makes it close to the performance of the human lungs, can be used as "artificial lungs", and extends its service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120079256A_ABST
    Figure CN120079256A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of membrane materials, in particular to an asymmetric PMP hollow fiber oxygenation membrane and a preparation method and application thereof. The PMP hollow fiber oxygenation membrane comprises a main body, one side of the main body is an inner surface facing an inner cavity, and the other side of the main body is an outer surface; the outer surface has a compact surface; the initial foaming point of hydrofluoroether of the oxygenation membrane is not lower than 2MPa, and the porosity of the oxygenation membrane is 40%-70%; the oxygen flux of the oxygenation membrane is 1 ml / (cm < 2 > * min * bar)-2.5 ml / (cm < 2 > * min * bar), and the separation ratio alpha (CO2 / O2) of carbon dioxide to oxygen of the oxygenation membrane is not lower than 1.8; the oxygenation membrane has appropriate oxygen flux and a high separation ratio alpha of carbon dioxide and oxygen, the oxygenation capacity of the oxygenation membrane is truly and greatly improved, the difference between the oxygenation membrane and the lung of the human body is shortened, and the oxygenation membrane can be used as an artificial lung to provide arterial blood for the organs of the human body and enable the organs of the human body to still work normally.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of membrane materials, and particularly relates to an asymmetric PMP hollow fiber oxygenation membrane, a preparation method thereof, and an application thereof. Background Art

[0002] The oxygenation membrane is a core component of an extracorporeal membrane oxygenation (ECMO) system, which is used to temporarily replace the cardiopulmonary function and provide extracorporeal respiration and blood circulation support for patients with severe cardiopulmonary failure. The main function of the oxygenation membrane is to perform two-way exchange of carbon dioxide and oxygen in the blood in vitro, simulating the function of human alveoli. Therefore, the oxygenation membrane must have good gas transmission ability. At the same time, since it is in direct contact with blood, it also needs to have excellent biocompatibility to reduce the risk of red blood cell hemolysis and thrombosis.

[0003] The poly(4-methyl-1-pentene) (PMP) material has high thermal stability, with a melting point as high as 240 °C and a Vicat softening point of 173 °C, and can be used at relatively high temperatures. The PMP material has a non-polar structure, so it has excellent electrical insulation properties. And the PMP material has strong resistance to most chemical substances and has excellent environmental and chemical resistance. Therefore, the PMP membrane is famous for its high gas permeability, good blood compatibility, and lasting anti-plasma leakage ability, and is a very important material in the medical field, especially in ECMO technology. The development of PMP oxygenation membranes has gone through three generations, evolving from solid silica membranes, microporous hollow fiber membranes to the current PMP hollow fiber membranes, gradually improving the clinical use effect. Currently, PMP hollow fiber membranes are used as the core components of ECMO in the treatment of patients with cardiopulmonary failure.

[0004] However, although the current PMP hollow fiber oxygenation membranes have relatively high oxygen fluxes, it is found in actual use that there is still a large gap between their oxygenation performance and that of the human lungs.

[0005] Therefore, it is necessary to further improve the oxygenation performance of PMP hollow fiber oxygenation membranes. Summary of the Invention

[0006] The purpose of the present invention is to overcome the above problems of the prior art, and provide an asymmetric PMP hollow fiber oxygenation membrane, a preparation method thereof, and an application thereof. The asymmetric PMP hollow fiber oxygenation membrane (hereinafter simply referred to as the oxygenation membrane) of the present invention has a suitable oxygen flux and a relatively high separation ratio α of carbon dioxide to oxygen, so that the oxygenation membrane has excellent oxygenation performance.

[0007] To achieve the above object, a first aspect of the present invention provides an asymmetric PMP hollow fiber oxygenation membrane, including a main body. One side of the main body is an inner surface facing the inner cavity, and the other side of the main body is an outer surface; the outer surface has a dense surface; the initial bubble point of the hydrogen fluorinated ether of the oxygenation membrane is not less than 2 MPa (for example, 2 MPa, 2.2 MPa, 2.4 MPa or 2.6 MPa), and the porosity of the oxygenation membrane is 40%-70% (for example, 40%, 45%, 50%, 55%, 60%, 65% or 70%); the oxygen flux of the oxygenation membrane is 1 ml / (cm 2 ×min×bar)-2.5 ml / (cm 2 ×min×bar) (for example, 1, 1.5, 2 or 2.5 ml / (cm 2 ×min×bar)), and the separation ratio α(CO 2 / O 2 ) of carbon dioxide to oxygen of the oxygenation membrane is not less than 1.8 (for example, 1.8, 2.1, 2.4, 2.6, 2.8 or 3).

[0008] In the related art, although the PMP (poly-4-methyl-1-pentene) hollow fiber oxygenation membrane has a relatively high oxygen flux, its oxygenation performance still has a large gap compared with that of the human lungs, that is, the oxygenation performance is insufficient. Through research, it is found that the gas diffusion in the oxygenation membrane mainly involves two mechanisms: solution diffusion and Knudsen diffusion. Among them, solution diffusion is that the gas "dissolves" in the oxygenation membrane and diffuses according to the concentration gradient; while Knudsen diffusion is the diffusion flow generated by the collision of gas molecules with the pore wall in a narrow space. In order to improve the oxygenation performance of the oxygenation membrane, the inventors of the present invention have conducted a large number of experiments and found that these two different mechanisms have a great influence on the gas flux and oxygenation performance of the oxygenation membrane. When the oxygenation membrane mainly relies on the Knudsen diffusion mechanism to achieve gas separation, generally, its gas flux is relatively large; and if the oxygenation membrane mainly relies on the solution diffusion mechanism to achieve gas separation, generally, its gas flux is lower than that of the Knudsen diffusion mechanism; both diffusions will affect the oxygenation performance of the membrane, but generally, the solution diffusion has a greater impact on the oxygenation performance of the membrane; in the present invention, by improving the structure of the oxygenation membrane, reasonable diffusion movement of gas is allowed, so as to improve its oxygenation performance, realize the rapid exchange of oxygen and carbon dioxide, and ensure sufficient oxygen flux.

[0009] In the field of oxygenation membranes, those skilled in the art generally believe that the higher the gas flux of the oxygenation membrane, the more oxygen the oxygenation membrane can transport per unit time (a high gas flux means that under the same conditions, the oxygenation membrane can deliver more oxygen to the blood), and thus the oxygenation efficiency is higher; therefore, when the oxygenation performance of the oxygenation membrane is insufficient, those skilled in the art usually improve the oxygenation performance by increasing the gas flux of the oxygenation membrane; however, through long-term research, it has been found that this understanding has a certain technical bias.

[0010] On the premise that the oxygen flux of the existing oxygenation membrane is higher than the oxygen gas transmission requirement, even if the oxygen flux is further increased, the oxygenation performance will basically not improve. For example, the partial pressure of oxygen, an important indicator of oxygenation performance, will increase very slowly or even decrease, and too high gas permeability may lead to too high gas content in the blood, forming bubbles, and may also affect the tolerance of the oxygenation membrane; through continuous research, we have found that for PMP oxygenation membranes, under the action of a specific membrane structure, only by controlling the oxygenation membrane to have a suitable oxygen flux to meet the oxygen transmission needs (that is, the oxygen flux does not need to be very high, and can even be lower than the oxygen flux of the existing oxygenation membrane), at this time, the higher the separation ratio of carbon dioxide to oxygen of the oxygenation membrane, the better the oxygenation performance, so that it can basically replace the function of the lung and meet the surgical application requirements.

[0011] First, the above-mentioned specific membrane structure means that the outer surface of the oxygenation membrane is dense, that is, there are almost no pores on the outer surface (the outer surface of the oxygenation membrane is the area where the oxygenation membrane is in direct contact with the blood, so the relevant characteristics of the outer surface have a greater impact on the performance of the oxygenation membrane), so that when various gases (such as oxygen, carbon dioxide, etc.) pass through the outer surface, gas exchange mainly relies on dissolution and diffusion. At this time, the separation ratio of carbon dioxide and oxygen will become higher, because the dense outer surface reduces the proportion of convective conduction of gases through visible pores in the oxygenation membrane. At this time, the vast majority of gases are "dissolved" in the dense PMP material, and then oxygen diffuses to the blood side, while carbon dioxide diffuses to the other side. Generally speaking, in the area where there are almost no pores in the oxygenation membrane, the PMP material has a higher conduction rate for carbon dioxide components than for oxygen, and the macroscopic manifestation is that the separation ratio of carbon dioxide to oxygen is high, that is, the PMP oxygenation membrane with a dense outer surface is conducive to increasing the separation ratio of carbon dioxide to oxygen (and this property of PMP is unique and completely different from other materials such as PP, and PP has almost no selectivity).

[0012] On the basis of the dense outer surface, we further regulate the initial bubble point size of the hydrogen fluorocarbon of the oxygenation membrane. Since the bubble point reflects the overall pore size of the oxygenation membrane; in conventional technologies, water or IPA (isopropyl alcohol) is generally used as the test liquid for the bubble point, while in the present invention, hydrogen fluorocarbon with a lower surface tension (surface tension of 13.6 mN / m) is selected as the test liquid for testing. When testing with a test liquid with such a low surface tension, we regulate the initial bubble point of the hydrogen fluorocarbon of the oxygenation membrane to be not less than 2 MPa, which indicates that the overall pore size of the oxygenation membrane is relatively small, further making dissolution-diffusion dominant, thus ensuring that the oxygenation membrane has a high separation ratio of carbon dioxide to oxygen. In addition, since the overall pore size of the oxygenation membrane is small, it is necessary to further regulate the overall porosity of the oxygenation membrane, preferably 40%-70%. Within the above range, it shows that the oxygenation membrane has a high porosity, which indicates that although the pore size of the oxygenation membrane is small, the number of pores is large. Such a structural design can enable the oxygenation membrane to maintain a certain oxygen flux to meet the usage requirements.

[0013] On the basis of the above membrane structure, we further regulate the gas flux and separation ratio of the oxygenation membrane (the gas flux and separation ratio also further play a role in defining the membrane structure, that is, the gas flux and separation ratio are not only the characterization of membrane performance, but more importantly, they also play a synergistic defining role in the overall membrane structure). In the present invention, the oxygen flux of the oxygenation membrane is regulated to be 1 ml / (cm 2 ×min×bar) - 2.5 ml / (cm 2 ×min×bar). Although the oxygen flux is relatively small, it meets the usage requirements; at this time, we regulate the separation ratio α(CO 2 / O 2 ) of the oxygenation membrane to be not less than 1.8. This is because we have found through research that the higher the separation ratio, on the one hand, it indicates that there are fewer visible pores or various defects (such as scratches) on the outer surface of the oxygenation membrane, and most gases are conducted through the cortex, that is, dissolution-diffusion conduction; on the other hand, we have found that a high separation ratio means high gas exchange efficiency. On the basis of a specific membrane structure, the oxygenation membrane can more effectively remove carbon dioxide from the blood (it is outstanding in the removal of carbon dioxide, which helps to reduce carbon dioxide toxicity and prevent hypercapnia), and provide oxygen to ensure that the partial pressure and saturation of oxygen in the patient's blood are maintained at the normal level required by the human body.

[0014] In summary, through the synergistic effect of regulating the outer surface of the PMP oxygenation membrane to be dense, the overall pore size of the oxygenation membrane to be relatively small (the initial bubble point of hydrogen fluorocarbon is not less than 2 MPa) and the high porosity (a large number of pores), we further regulate the oxygenation membrane to have a suitable oxygen flux and an extremely high separation ratio α of carbon dioxide to oxygen, truly greatly improving the oxygenation ability of the oxygenation membrane, shortening the gap with the human lungs, and truly being able to be used as an "artificial lung".

[0015] Meanwhile, we also found that due to the excellent self-tolerance of the PMP material, combined with the dense outer surface of the oxygenation membrane, the initial foaming point of the hydrofluoroether is not less than 2 MPa, and the oxygen flux is lower than that of the prior art (further indicating that the overall pore size of the membrane is very small and there are no large holes), which further ensures that the PMP oxygenation membrane has excellent plasma penetration time, can carry out oxygenation for a long time, has a long service life, has good practicability, and is suitable for application in extracorporeal life support (including cardiac surgery, cardiopulmonary transplantation bridging, emergency cardiopulmonary resuscitation, acute respiratory distress syndrome, cardiopulmonary organ transplantation, multiple organ failure, and pediatric congenital heart disease).

[0016] In the present invention, the dense surface has the conventional meaning in the art, which means that the hole area ratio on the outer surface is not higher than 1% (i.e., less than or equal to 1%); the hole area ratio on the outer surface can be measured by conventional methods in the art. Specifically, a scanning electron microscope (SEM) is used. In the electron micrograph at 10,000 times magnification, at least 5 outer surfaces with an area preferably of 2 μm × 2 μm are randomly selected (the area can also be adjusted accordingly), the hole area ratio is measured and calculated, and the average value is taken.

[0017] The test method for the initial foaming point is well-known in the art. For example, the procedures for these tests are explained in detail in ASTM F316-70 and ANS / ASTM F316-70 (re-approved in 1976), and these documents are incorporated herein by reference. The initial foaming point of the hydrofluoroether of the oxygenation membrane can be measured by conventional methods in the art. In the present invention, a hydrofluoroether with a surface tension of 13.6 mN / m is used as the test liquid; when bubbles start to appear on the oxygenation membrane, the pressure at this time is read as the initial foaming point. Generally, the larger the initial foaming point, the smaller the overall pore size of the oxygenation membrane. When the initial foaming point is too small, on the one hand, it indicates that the maximum pore size inside the oxygenation membrane is relatively large, and on the other hand, it may also indicate that there are defects inside the oxygenation membrane and the mechanical strength is relatively poor.

[0018] In the present invention, the porosity of the oxygenation membrane can be measured by conventional methods in the art, and in the present invention, it is measured by the mercury intrusion method.

[0019] In the present invention, the main body includes a cortical layer and a support layer; the side of the cortical layer facing away from the support layer is the outer surface, and the side of the support layer facing away from the cortical layer is the inner surface. The oxygenation membrane in the present invention is integrally formed and does not undergo a "composite" process. Therefore, by observing the membrane main body structure of the oxygenation membrane, it can be clearly seen that the oxygenation membrane has a two-layer structure with completely different pore structures. The layer with a relatively high cross-sectional pore ratio is the support layer, and the layer with a relatively low cross-sectional pore ratio is the cortical layer.

[0020] As a further improvement of the present invention, the average thickness of the skin layer is 0.1 μm - 3 μm (for example, 0.1 μm, 0.2 μm, 0.5 μm, 1 μm, 1.5 μm, 2 μm, 2.5 μm or 3 μm); the ratio of the average thickness of the skin layer to the average thickness of the oxygenation membrane is not greater than 5% (for example, 5%, 4.5%, 4%, 3.5%, 3%, 2.5%, 2%, 1.5%, 1%, 0.5% or 0.1%); the ratio of the standard deviation of the skin layer thickness to the average thickness of the skin layer is 0.01 - 1.5 (for example, 0.01, 0.05, 0.1, 0.5, 1 or 1.5).

[0021] Through repeated research, it is found that since the skin layer (the skin layer includes a dense outer surface) is the area with the smallest pores inside the oxygenation membrane (there are almost no holes in the skin layer), the average thickness of the skin layer has a great influence on both the oxygen flux of the oxygenation membrane and the separation ratio of carbon dioxide to oxygen. Moreover, we also found that the size of the average thickness of the skin layer is closely related to the initial bubble point and porosity of the hydrofluoroether of the oxygenation membrane, that is, the regulation of the average thickness of the skin layer (including the absolute average thickness and the relative average thickness) of the present invention is based on the initial bubble point and porosity of the hydrofluoroether; on the basis of a certain initial bubble point and porosity of the hydrofluoroether, we found that when the average thickness of the skin layer is too large (for example, greater than 3 μm), the time for carbon dioxide and oxygen to pass through the oxygenation membrane by solution diffusion will increase significantly, resulting in the inability of carbon dioxide to be discharged from the blood in time and the inability of oxygen to enter the blood in time, leading to a significant reduction in the oxygen flux, which will seriously affect its use; while when the average thickness of the skin layer is too small (for example, less than 0.1 μm), it will affect the degree of solution diffusion of the gas. Although it is beneficial to the improvement of the oxygen flux, the separation ratio of carbon dioxide to oxygen will decrease at this time; and the plasma penetration time of the oxygenation membrane will be greatly shortened, affecting the service life. At the same time, we hope that the ratio of the average thickness of the skin layer to the average thickness of the membrane is small, that is, the skin layer accounts for a small proportion in the oxygenation membrane, which is beneficial to having more holes and a higher porosity as a whole, further ensuring that the oxygenation membrane has a suitable oxygen flux. Therefore, it is necessary to limit the average thickness (absolute value) of the skin layer and the ratio of the average thickness of the skin layer to the average thickness of the oxygenation membrane (relative value). Finally, the present invention regulates the average thickness of the skin layer to be 0.1 μm - 3 μm, and the ratio of the average thickness of the skin layer to the average thickness of the oxygenation membrane is not greater than 5%.

[0022] Further research found that the uniformity of the cortex is also an important factor affecting the oxygen flux and the separation ratio of carbon dioxide and oxygen. When the average thickness of the cortex meets the conditions but the uniformity is poor, it will have a certain adverse effect on the separation ratio of carbon dioxide and oxygen and the gas flux of the oxygenation membrane. This is because the entire oxygenation membrane will participate in the separation selection of carbon dioxide and oxygen. Therefore, when the thickness of the cortex is uneven (the cortex is thicker in some positions and thinner in some positions), the separation ratio of carbon dioxide and oxygen in the position with thicker cortex will be too high, but the oxygen flux will be small; while the oxygen flux in the position with thinner cortex will be too large, but the separation of carbon dioxide and oxygen will be relatively low. In this case, the oxygen flux of the oxygenation membrane and the separation ratio of carbon dioxide and oxygen will be inconsistent, which will ultimately lead to unsatisfactory separation of carbon dioxide and oxygen and oxygen flux of the oxygenation membrane as a whole.

[0023] In addition, we unexpectedly found that when the oxygenation membrane has a cortical structure of appropriate thickness and the cortical thickness works relatively uniformly, the tolerance of the oxygenation membrane will be further significantly improved, the plasma penetration time will be greatly improved, the service life will be extended, and the application range will be further improved.

[0024] When measuring the average thickness of the oxygenated membrane, the membrane structure can first be comprehensively and carefully characterized by a scanning electron microscope; to ensure the accuracy and representativeness of the measurement results, multiple measurement sites (preferably more than 5) should be selected on the membrane structure, and the measurement sites should be kept uniformly and reasonably spaced. For example, according to the size and performance requirements of the actual membrane, the site spacing is preferably 1-5 microns (the specific value can be scientifically set according to the characteristics of the membrane and the industry standards to meet the measurement accuracy requirements in different application scenarios); after completing the site selection, for each site, a computer software (such as Matlab, NIS-Elements, etc.) is used for digital analysis and measurement. The thickness data corresponding to each site is obtained through the image recognition and data analysis functions of the software. Manual measurement can also be used to record the data of each measurement site with the help of professional measurement tools according to the standardized measurement process. In addition, the thickness data can be calculated for each site by measuring the outer diameter and inner diameter of the membrane and using the formula (outer diameter-inner diameter) ÷ 2. After completing the measurement and calculation of multiple sites, a series of thickness data obtained are statistically analyzed to calculate the arithmetic mean to determine the average thickness of the oxygenated film. Those skilled in the art will appreciate that, in addition to the above method, other suitable measurement methods may be used to obtain the parameter, and the measurement method listed here is for reference only.

[0025] In the present invention, the uniformity of the cortical thickness is reflected by the ratio between the standard deviation of the cortical thickness and the average thickness of the cortical layer. The smaller the ratio is, the more uniform the cortical thickness is.

[0026] During actual measurement, first, a scanning electron microscope (SEM) is used to perform high-resolution morphological characterization on the cross-sectional structure of the membrane to clearly present the microscopic structure of the cortex and provide an accurate image basis for subsequent thickness measurement. Then, a measurement area is randomly selected along the direction perpendicular to the membrane thickness. The length of the measurement line in this direction is key to control (it can be 10 μm or 5 μm, and the length of the measurement line can be flexibly determined according to the specific characteristics of the membrane and the measurement requirements). To ensure the independence and representativeness of the measurement data, a certain interval needs to be maintained between each measurement area (preferably not less than 5 μm). This interval setting is related to the size and distribution of the membrane pores, which can effectively avoid data correlation caused by too small an interval between areas and ensure that the measurement results meet statistical requirements and more truly reflect the overall thickness characteristics of the cortex. Then, for each selected measurement area, automated measurement is carried out with the help of professional computer software (such as Matlab, NIS-Elements, etc.), or manual measurement can be used. To ensure the accuracy and reliability of the measurement results, each area is measured multiple times, and the number of measurements is preferably more than 10 times. The specific number can be reasonably adjusted according to the actual situation such as the uniformity of the membrane and the measurement accuracy requirements. The cortical thickness data obtained from multiple measurements of the same area are summarized, and their arithmetic mean is calculated to serve as the average thickness of the cortex in this area. According to statistical principles, the standard deviation of the cortical thickness in this area is calculated. The standard deviation value of the cortical thickness in this area is compared with the average thickness to obtain the uniformity value of the cortical thickness in this area. To further improve the accuracy and reliability of the measurement results, preferably 3 measurement areas (or other numbers) that meet the above interval requirements are selected at different positions of the membrane, and the above measurement and calculation processes are repeated for each area to obtain the cortical thickness uniformity values of the 3 areas respectively. Finally, the arithmetic mean of these 3 uniformity values is taken, and this average value is the finally determined cortical thickness uniformity value, which can comprehensively and accurately reflect the uniformity characteristics of the entire oxygenation membrane cortex thickness.

[0027] In the present invention, the boundary line between the cortex and the support layer can be determined through the following steps:

[0028] First, a scanning electron microscope (SEM) is used to perform detailed morphological characterization on the part near the outer surface in the cross-section of the oxygenation membrane from the inner surface to the outer surface direction. To clearly present the microscopic features of the membrane structure, the magnification is accurately set to 20,000 times to obtain a high-quality mirror image.

[0029] On the obtained electron microscope image, careful observation is carried out along the direction from the outer surface to the inner surface. The side of the hole that can be clearly identified by the naked eye and is close to the outer surface is used as the key interface, which is defined as interface P1. The area covered from the outer surface to interface P1 is the cortex.

[0030] To more intuitively show the position of this interface,Figure 1 Figure 1 shows a scanning electron microscope (SEM) schematic diagram of a cross-section of the oxygenation membrane in one example of the present invention in the direction from the inner surface to the outer surface. In the figure, the interface pointed to by the red arrow is interface P1.

[0031] It should be specifically noted that due to the influence of various factors during the preparation of the oxygenation membrane, the distance from interface P1 to the outer surface is not fixed at different points on its cross-section. This means that the shape of interface P1 is not a simple circular arc curve, but may present a more complex geometric shape. At the same time, although the cortical thickness has relatively good uniformity as a whole, it is not absolutely uniform. At the microscopic level, there are certain differences in the cortical thickness at different positions and it is not the same everywhere.

[0032] Those skilled in the art should understand that in addition to the methods for determining the boundary between the cortex and the support layer and obtaining relevant parameters described above, other appropriate measurement means can also be adopted according to the actual situation to complete the same task. The measurement means introduced here is only for reference and aims to provide a feasible way for related research and applications.

[0033] As a further improvement of the present invention, the ratio of the standard deviation value of the cortical thickness to the average thickness of the cortex is 0.05 - 0.6.

[0034] As a further improvement of the present invention, for the ATR method infrared absorption spectrum of the outer surface, there is a first peak at 2940 cm -1 -2960 cm -1 and a second peak at 1455 cm -1 -1475 cm -1 ; the ratio of the peak area of the first peak to the peak area of the second peak is the selection coefficient X, and the selection coefficient X is 0.3 - 0.85 (for example, 0.3, 0.35, 0.4, 0.45, 0.5, 0.55, 0.6, 0.65, 0.7, 0.75, 0.8 or 0.85); the average thickness of the cortex is 0.3 μm - 2 μm.

[0035] As a further improvement of the present invention, the selection coefficient X is 0.45 - 0.7; the average thickness of the cortex is 0.4 μm - 1.5 μm.

[0036] Through further research, it is found that due to the different diameters and properties of CO 2 and O 2 molecules, therefore, the methyl group has different interactions with CO 2 and O 2The molecular capture abilities are different. When dissolution and diffusion dominate, by regulating the content of methyl groups on the outer surface, the separation ratio of carbon dioxide to oxygen of the oxygenation membrane can be further improved (the presence of methyl groups on the side chains in the PMP membrane will have certain effects on the arrangement of molecular chains, the formation of pore structures, and the diffusion paths of different gas molecules). Therefore, on the premise that the oxygenation membrane has a dense surface and has a specific initial foaming point and porosity of hydrofluoroether, the content of methyl groups on the outer surface is further regulated. According to research, in the ATR method infrared absorption spectrum of the outer surface, the first peak existing at 2940 cm -1 -2960 cm -1 can basically be the stretching vibration peak of methyl groups, and the second peak existing at 1455 cm -1 -1475 cm -1 is the internal standard peak. The ratio of the peak areas of the first peak and the second peak can reflect the content of methyl groups on the outer surface to a certain extent. The presence of methyl groups within a certain content range is beneficial to improving the gas selectivity and service life of the oxygenation membrane for the following reasons: First, due to the different diameters and properties of CO 2 and O 2 molecules, the methyl side chains in the PMP molecular structure have different capture abilities for CO 2 and O 2 molecules, which helps to improve the selectivity of the oxygenation membrane for CO 2 and O 2 . Second, the methyl side chains can increase the distance between molecular chains, thus creating more free volume, and these free volumes provide more diffusion channels for gas molecules, so the oxygen flux can be improved to a certain extent. Third, the presence of methyl side chains reduces the crystallinity of PMP. A lower crystallinity means a less ordered molecular structure, thus providing more space for gas molecules to transport. Fourth, the presence of methyl side chains makes the surface of the oxygenation membrane hydrophobic, thus reducing blood damage and improving gas exchange efficiency. However, the content of methyl side chains is not the more the better, because when the content of methyl groups is too high, the advantage of improving the gas flux of the oxygenation membrane is greater than the advantage of improving the separation ratio of carbon dioxide to oxygen. At this time, the improvement of the oxygen flux of the oxygenation membrane is greater than the improvement of the separation ratio of carbon dioxide to oxygen. Define the ratio of the peak area of the first peak to the peak area of the second peak as the selection coefficient X. When the selection coefficient X is within a specific range, it is beneficial to further improve the separation ratio of carbon dioxide to oxygen and improve the oxygenation ability.

[0037] In addition, further research finds that under the synergistic action of a suitable selection coefficient X and the average thickness of the cortex, it is more conducive to obtaining a higher separation ratio, further improving the oxygenation performance, and broadening the application range of the oxygenation membrane.

[0038] As a further improvement of the present invention, the ATR method infrared absorption spectrum of the outer surface has a third peak at 910 cm -1 -930 cm -1 The ratio of the peak area of the third peak to the peak area of the second peak is the crystallization coefficient Y, and the crystallization coefficient Y is 0.02 - 0.12 (such as 0.02, 0.03, 0.04, 0.05, 0.06, 0.07, 0.08, 0.09, 0.1, 0.11 or 0.12); the ratio of the average thickness of the cortex to the average thickness of the oxygenation membrane is 0.2% - 4%, and the porosity of the oxygenation membrane is 45% - 68%.

[0039] As a further improvement of the present invention, the crystallization coefficient Y is 0.04 - 0.08.

[0040] As a further improvement of the present invention, the ratio of the average thickness of the cortex to the average thickness of the oxygenation membrane is 0.4% - 2%.

[0041] The ATR method infrared absorption spectrum of the outer surface has a third peak at 910 cm -1 -930 cm -1 The third peak present is a crystallization peak, and the second peak present at 1455 cm -1 -1475 cm -1 is an internal standard peak. The crystallization peak on the outer surface can represent the crystallinity and crystallization behavior of the PMP material on the outer surface, and the ratio of the peak areas of the crystallization peak and the internal standard peak, the crystallization coefficient Y, can reflect to a certain extent the gas permeation and separation performance (gas permeation rate and separation ratio) and mechanical strength of the oxygenation membrane. Generally speaking, the crystalline region has relatively low gas permeability and has a greater impact on the gas separation ratio, while the non-crystalline region (i.e., the amorphous region) has high gas permeability; at the same time, the mechanical strength of the crystalline region is higher than that of the non-crystalline region. And the crystallization coefficient Y can indicate the thermal stability and chemical resistance of the outer surface of the oxygenation membrane. Since the outer surface is the region where the oxygenation membrane is in direct contact with the blood, on the basis of the relatively dense outer surface, further regulating the crystallization coefficient Y can further make the oxygenation membrane have a higher gas separation ratio and at the same time have excellent mechanical strength; in addition, it is found that under the synergistic action of the selection coefficient X and the crystallization coefficient Y, the gas separation ratio can be greatly improved, further improving the oxygenation performance of the oxygenation membrane, making its oxygenation performance closer to that of the human lungs, and can be applied in various extracorporeal life supports, with great economic value; at the same time, by regulating the ratio of the average thickness of the cortex to the average thickness of the oxygenation membrane and the porosity of the oxygenation membrane, this can further ensure the oxygen flux and mechanical strength of the oxygenation membrane to prevent structural deformation of the oxygenation membrane caused by mechanical stress during long-term use, which is beneficial to maintaining stable gas exchange.

[0042] As a further improvement of the present invention, the ATR method infrared absorption spectrum of the inner surface has a fourth peak at 910 cm -1 -930 cm -1 ; the ratio Z of the peak area of the fourth peak to the peak area of the third peak is 1.05 - 1.8, such as 1.05, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7 or 1.8.

[0043] As a further improvement of the present invention, Z is 1.1 - 1.55; the separation ratio α(CO 2 / O 2 ) of the oxygenation membrane is 2.1 - 3.

[0044] As mentioned above, the crystallization peak on the outer surface can represent the crystallinity and crystallization behavior of the PMP material on the outer surface. Therefore, the crystallization peak on the outer surface can reflect the gas permeation and separation performance of the outer surface (especially for the case of oxygen entering the blood from the membrane) and the mechanical strength, while the crystallization peak on the inner surface can reflect the gas permeation performance of the inner surface (mainly the removal of carbon dioxide) and the mechanical strength. The oxygenation membrane of the present invention can further improve the oxygen flux and the separation ratio of carbon dioxide and oxygen of the oxygenation membrane by regulating the ratio of the peak areas of the crystallization peaks on the inner and outer surfaces. This is because: their sizes will affect the opening conditions of the inner and outer surfaces. The oxygenation membrane of the present invention mainly separates carbon dioxide and oxygen through gas dissolution and diffusion, and thus has sufficient oxygen flux and a high separation ratio of carbon dioxide and oxygen. The crystallization peaks on the outer and inner surfaces reflect the sizes of the crystalline regions and non-crystalline regions on the outer and inner surfaces. When Z is too small (for example, less than 1.05), at this time, the crystalline region on the outer surface is too large relative to the inner surface. Although the outer surface has a high separation ratio of carbon dioxide and oxygen, the oxygen flux is too low, seriously affecting the use of the oxygenation membrane. When the crystallization coefficient Z is too large (for example, greater than 1.8), at this time, the crystalline region on the outer surface is too small relative to the inner surface, the separation ratio of carbon dioxide and oxygen on the outer surface is insufficient, and the mechanical strength of the outer surface is too low, or the inner surface has too many openings, the membrane pore diameter is too large, and the number is too many. The overall mechanical strength and toughness of the membrane are poor and insufficient to maintain the structural stability of the entire oxygenation membrane, especially the membrane pore stability.

[0045] As a further improvement of the present invention, the DSC crystallinity of the oxygenation membrane is 30% - 60% (such as 30%, 35%, 40%, 45%, 50%, 55% or 60%); the average thickness of the oxygenation membrane is 70 μm - 120 μm (such as 70 μm, 80 μm, 90 μm, 100 μm, 110 μm or 120 μm).

[0046] The DSC crystallinity of the oxygenation membrane can generally reflect the gas permeation and separation performance and mechanical strength of the oxygenation membrane. Also, the average thickness of the oxygenation membrane can reflect its gas permeation performance and mechanical strength. When the DSC crystallinity of the oxygenation membrane is small (e.g., less than 30%) and / or the average thickness of the oxygenation membrane is thin (e.g., less than 70 μm), the overall oxygen flux of the oxygenation membrane is large, but the separation ratio of carbon dioxide and oxygen and the mechanical strength are poor; while when the DSC crystallinity of the oxygenation membrane is large (e.g., greater than 60%) and / or the average thickness of the oxygenation membrane is thick (e.g., greater than 120 μm), the overall oxygenation membrane has a high separation ratio of carbon dioxide and oxygen and mechanical strength, but its oxygen flux is too low to meet the requirements of normal use; at the same time, the toughness of the oxygenation membrane is poor, and wire breakage is likely to occur during the weaving process. Therefore, by simultaneously regulating the DSC crystallinity and average thickness of the oxygenation membrane, the separation ratio of carbon dioxide and oxygen and the mechanical properties (tensile strength and elongation at break) are improved; and the combined action of appropriate DSC crystallinity and average thickness is also beneficial to improving the tolerance of the oxygenation membrane, thereby ensuring that the oxygenation membrane has excellent plasma penetration time.

[0047] In the present invention, the DSC crystallinity of the oxygenation membrane is measured by a DSC 1 - Mettler DSC differential scanning calorimeter.

[0048] As a further improvement of the present invention, the support layer has support fibers for forming a porous structure, and the SEM average width of the support fibers is 40 nm - 150 nm (e.g., 40 nm, 50 nm, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm, 110 nm, 120 nm, 130 nm, 140 nm or 150 nm); the cross-section of the support layer in the direction from the inner surface to the outer surface is a first cross-section, the first cross-section has a first hole, and the ratio of the SEM average pore diameter of the first hole to the SEM average width of the support fibers is (1.5 - 5):1, e.g., 1.5:1, 2:1, 2.5:1, 3:1, 3.5:1, 4:1, 4.5:1 or 5:1.

[0049] The average width of the support fibers in the support layer has a great influence on the mechanical strength of the oxygenation membrane and the diffusion path of gases. When the average width of the support fibers is too large (for example, greater than 150 nm), it is not conducive to gas diffusion and affects the movement speed of gases. However, at this time, the support force for the membrane pores is strong and the mechanical strength of the oxygenation membrane is high. When the average width of the support fibers is too small (for example, less than 40 nm), the support force for the membrane pores is weak at this time, resulting in insufficient mechanical strength of the oxygenation membrane. It is very difficult to weave the oxygenation membrane filaments into an oxygenation membrane cloth, and the practicality is greatly reduced. Moreover, it is not sufficient to maintain normal gas diffusion, and the membrane pores are prone to collapse and deformation. Also, the ratio of the SEM average pore diameter of the first holes to the SEM average width of the support fibers also has a great influence on the mechanical strength of the oxygenation membrane. When the ratio is too large (for example, greater than 5:1), the average pore diameter is relatively large compared to the average width, which is not conducive to the structural stability of the first holes themselves and the overall mechanical strength of the oxygenation membrane. When the ratio is too small (for example, less than 1.5:1), the average pore diameter is relatively small compared to the average width, and the overall mechanical strength of the oxygenation membrane is good, but it will affect gas permeation and is not conducive to the oxygen flux. Therefore, by coordinately regulating the SEM average width of the support fibers and the ratio of the SEM average pore diameter of the first holes to the SEM average width of the support fibers, the mechanical strength of the oxygenation membrane can be further improved and it can have an appropriate oxygen flux.

[0050] In the present invention, the SEM average width of the support fibers can be obtained by testing through conventional methods in the art. For example, using SEM, and then measuring and performing corresponding calculations using computer software (such as Matlab, NIS-Elements, etc.) or manually. Specifically as follows: First, use SEM to characterize the cross-section of the support layer to obtain the corresponding SEM image. Since the width of the support fibers on the support layer is roughly uniform, a certain area is selected, such as 100 μm 2 (10 μm multiplied by 10 μm) or 1 μm 2 (1 μm multiplied by 1 μm), and the specific area depends on the actual situation. Then, use computer software or manually measure the width of the support fibers on this area, perform several tests (preferably more than 10 times, and the specific number depends on the situation), and take the average value to obtain the SEM average width of the support fibers.

[0051] In the present invention, the SEM average pore diameter of the first holes can be obtained by testing with conventional methods in the art. For example, after using SEM to perform morphological characterization on the first cross-section of the oxygenation membrane, computer software (such as Matlab, NIS-Elements, etc.) or manual measurement is used, followed by corresponding calculations. The specific testing method is as follows: First, use SEM to characterize the first cross-section of the oxygenation membrane to obtain the corresponding SEM image. Since the pore diameter size distribution of the holes on the first cross-section of the oxygenation membrane is approximately uniform (in the support layer part), by selecting a certain area, for example, 100μm 2 (10μm multiplied by 10μm) or 1μm 2 (1μm multiplied by 1μm), the specific area depends on the actual situation. Then, use computer software or manually measure the pore diameter of the first holes on this area (when the shape of the first holes is similar to a circle, the pore diameter of the first holes refers to the diameter of the circle; when the shape of the first holes is similar to an ellipse, the pore diameter of the first holes refers to half of the sum of the major axis and the minor axis; when the shape of the first holes is relatively irregular, the longest line segment among the two-point line segments on the outer periphery of the hole can be considered as the major axis, and then measure the longest line segment among the two-point line segments on the outer periphery of the hole that is perpendicular to and intersects the major axis as the minor axis, and the pore diameter is still half of the sum of the major axis and the minor axis). Conduct several tests (preferably more than 10 times, and the specific number depends on the situation), and take the average value to obtain the SEM average pore diameter of the first holes.

[0052] As a further improvement of the present invention, the SEM average pore diameter of the first holes is 0.12μm - 0.45μm (for example, 0.12μm, 0.15μm, 0.2μm, 0.25μm, 0.3μm, 0.35μm, 0.4μm or 0.45μm); the pore density of the first holes is 30 holes / 25μm 2 -180 holes / 25μm 2 (for example, 30, 40, 50, 60, 70, 80, 90, 100, 110, 120, 130, 140, 150, 160, 170 or 180 holes / 25μm 2 ).

[0053] The SEM average pore diameter and pore density of the first holes are directly related to the mechanical strength and service life of the oxygenation membrane. An ideal support layer structure has smaller pore diameters but a larger number of pores. This is because a membrane with a smaller pore diameter can provide a larger gas exchange surface area, thereby improving the exchange efficiency of oxygen and carbon dioxide. When both of the above are within a specific range, it indicates that the support layer of the oxygenation membrane has smaller pore diameters and a larger number of pores, and there is a high degree of adaptability between the pore diameter and the number. At this time, the oxygenation membrane can ensure a relatively high separation ratio of carbon dioxide and oxygen, and also has a more appropriate oxygen flux. The oxygen flux will not be too low, better meeting the requirements of practical applications, and can ensure strong toughness and is not prone to wire breakage in practical applications.

[0054] In the present invention, the pore density of the first holes can be obtained by testing using conventional methods in the art. For example, SEM is used to characterize the morphology of the first cross-section of the oxygenation membrane, and then measured and calculated using computer software (such as Matlab, NIS-Elements, etc.) or manually. The specific testing method is as follows: First, use SEM to characterize the first cross-section of the oxygenation membrane to obtain the corresponding SEM image. Since the pore diameters of the holes on the first cross-section of the porous membrane are roughly uniform (in the support layer part), an area of 100μm 2 (10μm multiplied by 10μm) can be selected (the specific area depends on the situation), and then count the number of the first holes within this area. Conduct several tests (preferably more than 10 times, the specific number depends on the situation), and take the average value to obtain the pore density of the first holes. It should be noted that when 1 / 2 or more of the area of the first hole is within the selected 100μm 2 area, it is recorded as 1; when less than 1 / 2 of the area of the first hole is within the selected 100μm 2 area, it is recorded as 0.

[0055] As a further improvement of the present invention, several air-permeable holes are provided on the inner surface; the SEM average pore diameter of the air-permeable holes is 0.15μm - 0.8μm (for example, 0.15μm, 0.2μm, 0.25μm, 0.3μm, 0.35μm, 0.4μm, 0.45μm, 0.5μm, 0.55μm, 0.6μm, 0.65μm, 0.7μm, 0.75μm or 0.8μm); the hole area ratio of the air-permeable holes on the inner surface is 5% - 25%, for example, (5%, 10%, 15%, 20% or 25%).

[0056] The oxygenation membrane of the present invention is expected to have a dense outer surface and an inner surface with slightly larger pore sizes, so that it can not only meet the requirement of having a high separation ratio of carbon dioxide and oxygen for the oxygenation membrane, but also ensure a certain oxygen flux. The average SEM pore size of the breathable pores on the inner surface can affect the rate of gas (carbon dioxide and oxygen) entering and leaving the membrane to a certain extent. Within a certain range, the larger the average SEM pore size, the faster oxygen can pass through the support layer to reach the cortex for exchange with blood, and the faster carbon dioxide can be discharged through the support layer, thereby increasing the entry speed of oxygen and accelerating the discharge speed of carbon dioxide, which is beneficial for the process of quickly supplementing oxygen to patients and discharging carbon dioxide in emergency medical scenarios. At the same time, the oxygenation membrane of the present invention also needs to have an appropriate number of breathable pores on its inner surface, that is, the pore area ratio of the breathable pores on the inner surface needs to be appropriate. Such a setting can cooperate with a specific average SEM pore size. On the premise of a specific average SEM pore size, further limiting the pore area ratio of the breathable pores is more conducive to increasing the surface area of gas exchange, thereby improving the gas exchange efficiency of the oxygenation membrane; at the same time, it can also ensure the overall mechanical strength, durability and stability of the oxygenation membrane. At the same time, when the above specific average SEM pore size and pore area ratio are met, the inner surface has higher pressure resistance and high industrial practicability.

[0057] During the preparation of the oxygenation membrane, in the direction perpendicular to the membrane thickness (if the membrane is in the form of a flat membrane, this direction is the planar direction; if the membrane is in the form of a hollow fiber membrane, this direction is perpendicular to the radial direction), its various characteristics such as pore size are approximately uniform and basically consistent. Therefore, the overall pore size on this plane can be reflected by the pore size in a partial area on the corresponding plane. In the present invention, the average SEM pore size of the breathable pores (when the shape of the breathable pores is similar to a circle, the pore diameter of the breathable pores refers to the diameter of the circle; when the shape of the breathable pores is similar to an ellipse, the pore diameter of the breathable pores refers to half of the sum of the major axis and the minor axis; when the shape of the breathable pores is relatively irregular, it can be considered that the longest line segment among the two-point line segments on the outer periphery of the pore is used as the major axis, and then the longest line segment among the line segments connecting two points on the outer periphery of the pore that intersect perpendicularly to the major axis is measured as the minor axis, and the pore diameter is still half of the sum of the major axis and the minor axis) and the pore area ratio of the breathable pores on the inner surface can be obtained by conventional methods in the art. For example, after using SEM to characterize the morphology of the inner surface of the oxygenation membrane, it can be measured and calculated by using computer software (such as Matlab, NIS-Elements, etc.) or manually. The specific test method for the average SEM pore size of the breathable pores is as follows: First, use SEM to characterize the inner surface of the oxygenation membrane to obtain the corresponding SEM image. Since the pore sizes of the breathable pores on the inner surface of the oxygenation membrane are approximately uniform, a certain area is selected, such as 100μm 2 (10μm multiplied by 10μm) or 1μm2 (1 μm by 1 μm), the specific area depends on the actual situation. Then use computer software or manually measure the pore diameter of the air-permeable holes on this area, conduct several tests (preferably more than 10 times, and the specific number of times depends on the situation), and take the average value to obtain the average SEM pore diameter of the air-permeable holes.

[0058] The test method for the pore area ratio of the air-permeable holes on the inner surface is as follows: First, use SEM to characterize the inner surface of the oxygenation membrane to obtain the corresponding SEM image, such as 100 μm 2 (10 μm by 10 μm) or 1 μm 2 (1 μm by 1 μm), the specific area depends on the actual situation. Then use computer software or manually measure the total area of the air-permeable holes on this area, conduct several tests (preferably more than 10 times, and the specific number of times depends on the situation), so as to obtain the pore area ratio of the air-permeable holes on the inner surface.

[0059] As a further improvement of the present invention, the ratio of the average SEM pore diameter of the air-permeable holes to the average SEM pore diameter of the first holes is (1.2 - 3):1, for example, 1.2:1, 1.5:1, 2:1, 2.5:1 or 3:1.

[0060] By defining the ratio of the average SEM pore diameter of the air-permeable holes to the average SEM pore diameter of the first holes as (1.2 - 3):1, it shows that the average SEM pore diameter of the air-permeable holes is slightly larger than that of the first holes, but not too large. This is more conducive to oxygen entering the support layer through the inner surface, thereby improving the gas exchange rate, and at the same time ensuring that the oxygenation membrane has high toughness.

[0061] As a further improvement of the present invention, there are several surface fibers on the inner surface for supporting the air-permeable holes. The average SEM width of the surface fibers is 60 nm - 250 nm (for example, 60 nm, 70 nm, 80 nm, 90 nm, 100 nm, 110 nm, 120 nm, 130 nm, 140 nm, 150 nm, 160 nm, 170 nm, 180 nm, 190 nm, 200 nm, 210 nm, 220 nm, 230 nm, 240 nm or 250 nm), and the ratio of the average SEM width of the surface fibers to the average SEM pore diameter of the air-permeable holes is not less than 0.1 (for example, 0.1, 0.15, 0.2, 0.25 or 0.3).

[0062] By further limiting the ratio of the average SEM width of the surface fibers to the average SEM pore diameter of the air-permeable pores to be not less than 0.1, the oxygenation membrane of the present invention can further balance the gas exchange efficiency and mechanical strength, ensuring that the oxygenation membrane maintains good mechanical stability while having high gas exchange capacity. When the ratio is too large, the average SEM width of the surface fibers is relatively large compared to the average SEM pore diameter of the air-permeable pores, and the gas exchange efficiency decreases. The too-small pore diameter will limit the gas diffusion rate, resulting in insufficient oxygen flux. When the ratio is too small, the average SEM pore diameter of the air-permeable pores is relatively large compared to the average SEM width of the surface fibers, and the surface fibers are not sufficient to stably support the air-permeable pores, leading to poor overall structural stability of the oxygenation membrane and prone to problems such as rupture and tearing during use. It may also cause uneven gas diffusion in the oxygenation membrane, with excessive gas exchange in some areas and relatively insufficient in other areas, affecting the overall oxygenation effect.

[0063] In the present invention, the average SEM width of the surface fibers can be obtained by testing using conventional methods in the art, such as using SEM and then measuring and performing corresponding calculations using computer software (such as Matlab, NIS-Elements, etc.) or manually. Specifically as follows: First, use SEM to characterize the inner surface to obtain the corresponding SEM image. Since the width of the surface fibers on the inner surface is approximately uniform, a certain area is selected, such as 100μm 2 (10μm multiplied by 10μm) or 1μm 2 (1μm multiplied by 1μm), and the specific area depends on the actual situation. Then, use computer software or manually measure the width of the surface fibers on this area, perform several tests (preferably more than 10 times, and the specific number depends on the situation), and take the average value to obtain the average SEM width of the surface fibers.

[0064] As a further improvement of the present invention, the oxygenation membrane further satisfies one or more of the following characteristics:

[0065] (1) The tensile strength of the oxygenation membrane is not less than 80 cN, and the elongation at break is not less than 80%;

[0066] (2) The plasma penetration time of the oxygenation membrane is not less than 48 hours, preferably not less than 96 hours;

[0067] (3) Under the condition of treating blood with an oxygenation membrane flow rate of 5 L / min at 1.6 m 2 The oxygen saturation of arterial blood is not less than 99%, the oxygen partial pressure is not less than 150 mmHg, and the carbon dioxide partial pressure is not higher than 46 mmHg; and the end-tidal carbon dioxide concentration is not less than 29 mmHg.

[0068] The oxygenation membrane of the present invention has undergone various performance tests and obtained the following results: the tensile strength of the oxygenation membrane is not less than 80 cN; the elongation at break of the oxygenation membrane is not less than 80%; this shows that the oxygenation membrane of the present invention has good mechanical properties and high industrial practical value, and can fully meet the market demand. The plasma penetration time of the oxygenation membrane is not less than 48 hours; preferably not less than 96 hours. This shows that the oxygenation membrane of the present invention is more reliable to use and has a long service life. At 1.6m 2 When the blood flow rate through the oxygenation membrane is 5 L / min, the oxygen saturation of arterial blood is not less than 99%, the partial pressure of oxygen is not less than 150 mmHg, and the partial pressure of carbon dioxide is not higher than 46 mmHg; and the end-tidal carbon dioxide concentration is not less than 29 mmHg. This shows that the oxygenation membrane of the present invention has appropriate oxygen and carbon dioxide mass transfer rates and a high separation ratio, so that carbon dioxide in the blood can be quickly discharged, and oxygen can enter the blood at an appropriate speed to achieve ideal gas exchange; and through the oxygenation performance test, the oxygenation membrane has high oxygenation performance, high oxygen saturation, and high partial pressure of oxygen (the higher the partial pressure of oxygen, the better the oxygenation performance), the partial pressure of carbon dioxide in the blood is very low, and the partial pressure of carbon dioxide at the end of respiration is very high, indicating that carbon dioxide can be completely discharged from the blood as quickly as possible, truly realizing extracorporeal membrane oxygenation and / or extracorporeal carbon dioxide removal, and realizing extracorporeal life support.

[0069] The second aspect of the present invention provides a method for preparing the asymmetric PMP hollow fiber oxygenation membrane described in the first aspect of the present invention.

[0070] The preparation method includes the following steps:

[0071] Step 1: Heat and plasticize PMP; dissolve it in the weak solvent compound A and carry out kneading to obtain a homogeneous casting solution; wherein, the solid content (mass content) of PMP in the casting solution is 30%-49% (for example, 30%, 35%, 40%, 45% or 49%); the compound A includes at least one of N,N-bis-2-hydroxyethyl hexadecylamine, methyl-12-hydroxystearic acid, paraffin oil, dibutyl sebacate, dibutyl phthalate, diethyl phthalate and oleic acid amide;

[0072] Step 2: Extrude the casting solution under the die head to form a molded product with an inner surface and an outer surface;

[0073] Step 3: Carry out preliminary phase separation of the molded product in the air section, and the compound A volatilizes to form a precursor of the skin layer;

[0074] Step 4: Cool and phase-separate the preliminarily phase-separated molded product with coolant compound B to obtain a green film with a skin layer; wherein, the temperature for the cooling and phase separation is 3°C - 40°C (such as 3°C, 5°C, 10°C, 20°C, 30°C or 40°C), and the residence time for the cooling and phase separation is 0.5 s - 10 s (such as 0.5 s, 1 s, 2 s, 3 s, 4 s, 5 s, 6 s, 7 s, 8 s, 9 s or 10 s);

[0075] Compound B includes at least one of polyethylene glycol 400, glycerol, pure water, peanut oil, glycerol diacetate, dimethyl phthalate, dimethyl carbonate and glycerol triacetate;

[0076] Step 5: Remove compound A and compound B from the green film to obtain a raw film;

[0077] Step 6: Dry and shape the raw film to obtain the asymmetric PMP hollow fiber oxygenation membrane.

[0078] As a further improvement of the present invention, the temperature for the mixing is 210°C - 270°C (such as 210°C, 220°C, 230°C, 240°C, 250°C, 260°C or 270°C), and the temperature for the extrusion in Step 2 is 220°C - 250°C (such as 220°C, 230°C, 240°C or 250°C).

[0079] As a further improvement of the present invention, in Step 3, the temperature of the air section is 10°C - 80°C (such as 10°C, 20°C, 30°C, 40°C, 50°C, 60°C, 70°C or 80°C), and the time for the preliminary phase separation is 1 ms - 30 ms (such as 1 ms, 5 ms, 10 ms, 15 ms, 20 ms, 25 ms or 30 ms); the preliminary phase separation is accompanied by a blowing treatment, the blowing speed is 5 m / min - 20 m / min (such as 5, 10, 15 or 20 m / min), and the blowing gas is at least one of nitrogen, argon and helium.

[0080] As a further improvement of the present invention, the pressure for the mixing is 2 MPa - 5 MPa, such as 2 MPa, 3 MPa, 4 MPa or 5 MPa.

[0081] As a further improvement of the present invention, in Steps 3 and 4, the running speed of the molded product is 40 m / min - 80 m / min, such as 40 m / min, 50 m / min, 60 m / min, 70 m / min or 80 m / min.

[0082] As a further improvement of the present invention, the temperature of the cooling and phase separation is 10°C - 50°C lower than the temperature of the air section, for example, 10°C, 20°C, 30°C, 40°C or 50°C.

[0083] As a further improvement of the present invention, the step of removal in step five includes cleaning extraction. The temperature of the cleaning extraction is 60°C - 80°C (for example, 60°C, 65°C, 70°C, 75°C or 80°C), and the time of the cleaning extraction is 4h - 8h (for example, 4h, 5h, 6h, 7h or 8h); the cleaning extraction uses an extraction liquid, and the extraction liquid includes at least one of isopropanol, ethanol, isobutanol and acetone.

[0084] As a further improvement of the present invention, the temperature of the extrusion is 5°C - 25°C lower than the temperature of the mixing, for example, 5°C, 10°C, 15°C, 20°C or 25°C.

[0085] As a further improvement of the present invention, the drying and shaping includes heat drying and heat shaping.

[0086] As a further improvement of the present invention, the heat drying is carried out first, and then the heat shaping is carried out.

[0087] As a further improvement of the present invention, the temperature of the heat drying is 40°C - 60°C, for example, 40°C, 50°C or 60°C. The time of the heat drying is 60min - 120min, for example, 60min, 70min, 80min, 90min, 100min, 110min or 120min.

[0088] As a further improvement of the present invention, the temperature of the heat shaping is 120°C - 160°C, for example, 120°C, 130°C, 140°C, 150°C or 160°C. The time of the heat shaping is 5s - 20s, for example, 5s, 10s, 15s or 20s.

[0089] The present invention prepares an asymmetric PMP (poly-4-methyl-1-pentene) hollow fiber oxygenation membrane by the thermally induced phase separation method. When preparing the oxygenation membrane, the first step is to heat and plasticize PMP and then dissolve it in the weak solvent compound A. Kneading is carried out at a temperature of 210°C - 270°C and a kneading pressure of 2 MPa - 5 MPa, so that PMP is evenly dispersed in compound A, facilitating the formation of a uniform casting solution and thus conducive to obtaining an oxygenation membrane with good integrity and uniformity. As one of the innovative points of the present invention, a suitable casting solution system has been discovered. The solvent therein is only the weak solvent compound A (compound A can be only one substance or a mixture of multiple substances). Different from the traditional solvent system, the current traditional solvent system is generally a strong solvent or a strong solvent + non-solvent, while the present invention only has a weak solvent. In the present invention, a strong solvent means that at 1 atmosphere (101.325 kPa), a polymer with a solid content of 25% can be completely dissolved at a temperature of T1, where T1 ≤ the melting point of the polymer at 1 atmosphere + 30°C; that is, a strong solvent means that a polymer with a solid content of 25% can be completely dissolved in this solvent when the temperature is within 30°C above the melting point of the polymer (within the temperature range of Tm + 30°C). A weak solvent means that at 1 atmosphere (101.325 kPa), a polymer with a solid content of 25% can be completely dissolved at a temperature of T2, where the melting point of the polymer at 1 atmosphere + 30°C < T2 ≤ the melting point of the polymer at 1 atmosphere + 50°C; that is, a weak solvent means that a polymer with a solid content of 25% can be completely dissolved in this solvent when the temperature is within 50°C above the melting point of the polymer (within the temperature range of Tm + 30°C to Tm + 50°C).

[0090] More preferably, Compound A includes at least one of N,N-bis(2-hydroxyethyl)hexadecylamine, methyl-12-hydroxystearic acid, paraffin oil, dibutyl sebacate, dibutyl phthalate, diethyl phthalate, and oleamide. That is, the solvent system of the present invention is a "weak" solvent system. On the one hand, it can fully dissolve PMP at a certain temperature. On the other hand, it can combine with the subsequent corresponding phase separation process (carrying out appropriate preliminary phase separation and cooling phase separation) to form the pore structure required for the oxygenation membrane of the present invention (optimally forming a thin and uniform skin layer and a support layer with small and numerous pores), and corresponding pore size (the initial foaming point of hydrofluoroether is not less than 2 MPa) and porosity and other characteristics; in addition, we hope that the solid content of PMP in the casting solution is very high, and the solid content is 30%-49% (preferably 35%-45%), which is conducive to rapid phase separation, so that the whole membrane has a smaller pore size and the skin layer basically has no pores and has a dense outer surface, which is not only conducive to improving the separation ratio of carbon dioxide and oxygen, but also ensures the plasma penetration time, and also has a good porosity (if the solid content is too low, it is not easy to form small pores, and even it is easy to cause pores with a certain pore size on the skin layer, especially the outer surface; while if the solid content is too large, the film-making difficulty increases greatly, and at the same time the porosity will be significantly reduced, and the overall toughness of the membrane is also poor); of course, if necessary, other substances such as antioxidants, nucleating agents, fillers, and similar substances can also be used as additives.

[0091] In the second step, the casting solution is extruded under the die head to form a molded product with an inner surface and an outer surface; this molded product is a hollow fiber membrane; the casting solution is extruded through the middle cavity of the hollow fiber die head, and the middle cavity serves as an inner core, which plays a role in forming and stabilizing the hollow fiber membrane cavity. During the extrusion process, the extruded hollow fiber membrane (molded product) has a surface facing the cavity, that is, the inner surface, and a surface opposite to the cavity, that is, the outer surface, which is separated from the inner surface by the hollow fiber membrane wall; in the present invention, the inner core used during the extrusion of the hollow fiber membrane is in the form of a gas, preferably nitrogen, argon, or other inert gases, so as to ensure that the pressure inside the hollow fiber membrane cavity is balanced with the external pressure, thereby stabilizing the cavity of the hollow fiber membrane. In the present invention, the preferred extrusion temperature is 220°C - 250°C; more preferably, the extrusion temperature is 5°C - 25°C lower than the mixing temperature; such a setting is more conducive to ensuring the uniformity of the molded product during extrusion (for example, the overall thickness of the membrane is uniform, which is conducive to the uniform thickness of the skin layer, for example, the uniformity of the overall microstructure of the membrane, and it is not easy to generate large-pore holes in the support layer). Combining with the subsequent phase separation process, it will reduce the defects on the outer surface, and at the same time is more conducive to obtaining a relatively uniform skin layer in thickness, and is conducive to ensuring a relatively high foaming point of the hydrofluoroether of the membrane and a small overall pore size of the membrane; thereby further improving the separation ratio.

[0092] In order to obtain an oxygenation membrane with a dense outer surface, an initial foaming point and a porosity of the hydrofluoroether within a specific range, and an oxygen flux and a separation ratio of carbon dioxide to oxygen within a specific range, it is also necessary to coordinately control Step 3 and Step 4. As one of the creativities of the present invention, Step 3 is to perform preliminary phase separation in the air section. Under the synergistic action of the appropriate preliminary phase separation in the present invention and the cooling phase separation in Step 4, it is beneficial to obtain an ideal outer surface, that is, a dense surface (there are almost no defects such as scratches on the outer surface), and at the same time further has an appropriate crystallization coefficient and selectivity coefficient; and an ideal skin structure, with a relatively thin and uniform skin.

[0093] In the present invention, preliminary phase separation is carried out in the air section to enable the compound A in the molded product to volatilize appropriately to form a skin precursor; preferably, by controlling the temperature and time of the air section in the present invention, the volatilization rate of the compound A can be regulated, so that the content of the compound A in the part near the outer surface is less than that in the part far from the outer surface, thereby increasing the solid content in the area near the outer surface, which is more helpful for accelerating phase separation and then forming the outer surface and skin structure required by the present invention; at the same time, since the pre-phase separation time is extremely short, the volatilization amount of the compound A is very small, so it is beneficial to finally form a relatively thin skin, which is beneficial to improving the separation ratio and will not cause the oxygen flux to be too low; in addition, while pretreating in the air section, blowing treatment is also carried out coordinately. Under the action of appropriate blowing treatment (preferably, controlling the ratio of the blowing speed to the running speed of the molded product to be 1:(3-11.5), which is beneficial to the ideal volatilization of the compound A in a short time), the compound A can be volatilized effectively and uniformly, so that the skin thickness will be more uniform and the methyl group and crystallization condition on the outer surface will be more ideal.

[0094] The fourth step is to cool and phase-separate the formed product with a coolant to obtain a green film with a skin layer. When phase-separating and curing the formed product, the selection of several factors such as the type of coolant, the cooling temperature, and the cooling residence time is extremely crucial. These factors determine whether an oxygenation membrane with an ideal membrane structure and performance can be finally obtained. Based on the corresponding casting solution and a suitable pre-phase separation process, the coolant in the present invention is a non-solvent compound B (even at a very high temperature, PMP is hardly soluble in this substance), and the compound B includes at least one of polyethylene glycol 400, glycerol, pure water, peanut oil, glycerol diacetate, dimethyl phthalate, dimethyl carbonate, and glycerol triacetate. That is, the present invention is a system of a weak solvent + non-solvent coolant, which helps the overall rapid phase separation of the membrane. At the same time, the temperature and time in the cooling phase separation are further regulated. With the cooperation of a suitable coolant, a lower cooling temperature, and a shorter residence time, the overall phase separation speed of the membrane is very fast. At this time, the support layer is conducive to forming a structure with small and numerous pores. The area near the outer surface has a higher solid content and a lower content of the weak solvent compound A after air-section pretreatment. Combining with the corresponding phase separation speed, a thin and uniform skin layer structure with a dense outer surface is finally formed, and there are almost no pores inside the skin layer. Through the coordinated control of the above steps, an oxygenation membrane with a high carbon dioxide and oxygen separation ratio of the present invention can be obtained. In steps three and four, the running speed of the formed product is 40 m / min - 80 m / min. By regulating the running speed of the membrane filaments, the thickness and uniformity of the skin layer, as well as the crystallization condition of the outer surface, can be further controlled.

[0095] The fifth step is to remove compound A and compound B from the green film to obtain the original membrane. The purpose is to remove compound A and compound B as much as possible, reduce the residue of substances, and not introduce other impurities, ensure the biocompatibility of the oxygenation membrane, and minimize the secondary harm to patients. In the removal step, at least one of isopropanol, ethanol, isobutanol, and acetone is selected as the extraction liquid, and the temperature is 60°C - 80°C, and the time is 4 h - 8 h. It can ensure that compound A and compound B in the membrane are removed as much as possible, reduce the internal stress and defects in the membrane, and thus improve the uniformity and mechanical properties of the membrane.

[0096] The sixth step is to dry and shape the original membrane. Drying and shaping is a process of treating the oxygenation membrane at a certain temperature to improve its dimensional stability (stabilizing the membrane pore structure and pore size) and physical properties. During the drying and shaping process, the molecular chains of the membrane material in the oxygenation membrane may rearrange, thus affecting the structure and uniformity of the skin layer. Appropriate drying and shaping conditions can improve the physical properties and dimensional stability of the membrane material, while inappropriate drying and shaping conditions may lead to local overheating or excessive shrinkage of the membrane material, thereby affecting the uniformity of the skin layer; and it is easy to cause the toughness of the PMP oxygenation membrane to be very poor, prone to filament breakage, and not practical; in the present invention, a special drying and shaping process is adopted according to the corresponding membrane structure - first drying at a lower temperature for a longer time, and then heat setting at a higher temperature for a very short time; preferably, the temperature control of the heat drying is 40°C - 60°C, and the time is 60 min - 120 min; while the temperature of the heat setting is 120°C - 160°C, and the time is 5 s - 20 s. The temperature of the heat drying is much lower than that of the heat setting, and the time of the heat drying is much longer than that of the heat setting. The long-time heat drying at a lower temperature helps to gradually remove the extraction liquid and possibly the remaining compounds A and B, while reducing the structural defects caused by rapid drying; and the short-time heat setting at a higher temperature helps to fix the structure of the membrane filaments and avoid excessive pore structure due to overheat treatment. Through the synergistic effect of the two, the structure and performance of the PMP oxygenation membrane can be effectively controlled, improving its tolerance and oxygenation efficiency, while maintaining the membrane filaments with good toughness. It should be noted that in steps five and six, there is no need to stretch the membrane filaments, because after stretching treatment, the PMP membrane filaments will shrink instead, affecting their service life.

[0097] The third aspect of the present invention provides an application of an asymmetric PMP hollow fiber oxygenation membrane, and the asymmetric PMP hollow fiber oxygenation membrane is used for extracorporeal membrane oxygenation and / or extracorporeal carbon dioxide removal. The asymmetric PMP hollow fiber oxygenation membrane includes the asymmetric PMP hollow fiber oxygenation membrane described in the first aspect of the present invention or the asymmetric PMP hollow fiber oxygenation membrane prepared by the preparation method described in the second aspect of the present invention.

[0098] Through the above technical solutions, the present invention has at least the following advantages compared with the prior art:

[0099] (1) The oxygenation membrane of the present invention has a high separation ratio of carbon dioxide and oxygen and an appropriate oxygen flux;

[0100] (2) The oxygenation membrane of the present invention has high mechanical strength and a long service life.

[0101] The endpoints and any values in the ranges disclosed herein are not limited to the exact ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, between the endpoint values of each range and individual point values, and between individual point values can be combined with each other to obtain one or more new numerical ranges, and these numerical ranges should be regarded as specifically disclosed herein. Description of the Drawings

[0102] Figure 1 Shown is a schematic scanning electron microscope (SEM) diagram of a cross-section of an oxygenation membrane in the direction from the inner surface to the outer surface in an example of the present invention.

[0103] Figure 2 Shown is a schematic scanning electron microscope (SEM) diagram of the outer surface of the oxygenation membrane prepared in Example 1, where the magnification is 20000×.

[0104] Figure 3 Shown is a schematic scanning electron microscope (SEM) diagram of a cross-section of the oxygenation membrane prepared in Example 1 in the direction from the inner surface to the outer surface, where the magnification is 5000×.

[0105] Figure 4 Shown is a schematic scanning electron microscope (SEM) diagram of the middle region of the support layer of the oxygenation membrane prepared in Example 1, where the magnification is 10000×.

[0106] Figure 5 Shown is a schematic scanning electron microscope (SEM) diagram of the support layer (near the inner surface) of the oxygenation membrane prepared in Example 1, where the magnification is 5000×.

[0107] Figure 6 Shown is a schematic scanning electron microscope (SEM) diagram of the inner surface of the oxygenation membrane prepared in Example 3, where the magnification is 1000×.

[0108] Figure 7 Shown is a schematic scanning electron microscope (SEM) diagram of the inner surface of the oxygenation membrane prepared in Example 3, where the magnification is 5000×.

[0109] Figure 8 Shown is a schematic diagram of the device for testing the oxygenation performance of the oxygenation membrane. Detailed Description of the Embodiments

[0110] The present invention will be described in detail below through embodiments. The embodiments described in the present invention are only a part of the embodiments of the present invention, rather than all of the embodiments. All other embodiments obtained by those of ordinary skill in the art based on the embodiments in the present invention without creative efforts fall within the scope of protection of the present invention.

[0111] In the following examples, unless otherwise specified, the materials used are commercially available analytical pure grade.

[0112] The following examples are used to illustrate the asymmetric PMP hollow fiber oxygenation membrane of the present invention.

[0113] Example 1

[0114] The oxygenation membrane was prepared according to the following method:

[0115] Step 1: Heat and plasticize PMP; dissolve it in the weak solvent compound A (N,N-bis-2-hydroxyethyl hexadecylamine) and conduct kneading to obtain a homogeneous casting solution; wherein, the solid content of PMP in the casting solution is 40%; the temperature of the kneading is 242 °C, and the pressure of the kneading is 3.5 MPa.

[0116] Step 2: Extrude the casting solution obtained in Step 1 under the die head to form a molded product with an inner surface and an outer surface; wherein, the extrusion temperature is 230 °C; the extrusion temperature is 12 °C lower than the kneading temperature.

[0117] Step 3: Conduct preliminary phase separation on the molded product obtained in Step 2 in the air section to volatilize compound A and form a precursor of the skin layer; wherein, the temperature of the air section is 50 °C, the time of the preliminary phase separation is 15 ms, the preliminary phase separation is accompanied by blowing treatment, the blowing speed is 10 m / min, and the blowing gas is nitrogen.

[0118] Step 4: Cool and phase-separate the molded product after the preliminary phase separation with the coolant non-solvent compound B (glycerol diacetate) to obtain a green film with a skin layer; wherein, the temperature of the cooling and phase separation is 22 °C, and the time of the cooling and phase separation is 5 s; the temperature of the cooling and phase separation is 28 °C lower than the temperature of the air section.

[0119] Among them, in Step 3 and Step 4, the running speed of the molded product is 60 m / min.

[0120] Step 5: Remove compound A and compound B from the green film to obtain a raw membrane; wherein, the removal step includes washing and extraction, the temperature of the washing and extraction is 70 °C, the time is 6 h, and the extraction liquid is isopropanol.

[0121] Step 6: Dry and shape the raw membrane obtained in Step 5 to obtain an asymmetric PMP hollow fiber oxygenation membrane; wherein, the drying and shaping include heat drying and heat setting; the temperature of the heat drying is 50 °C, and the time is 90 min; the temperature of the heat setting is 140 °C, and the time is 12 s. Among them, the average thickness of the oxygenation membrane is 90 μm.

[0122] Example 2

[0123] Prepare the oxygenation membrane according to the following method:

[0124] Step 1: Heat and plasticize PMP; dissolve it in the weak solvent compound A (dibutyl sebacate) and carry out kneading to obtain a homogeneous casting solution; wherein, the solid content of PMP in the casting solution is 45%; the temperature of the kneading is 225 °C, and the pressure of the kneading is 4.5 MPa.

[0125] Step 2: Extrude the casting solution obtained in Step 1 under the die head to form a molded product with an inner surface and an outer surface; wherein, the temperature of the extrusion is 220 °C; the extrusion temperature is 5 °C lower than the kneading temperature.

[0126] Step 3: Carry out preliminary phase separation on the molded product obtained in Step 2 in the air section to volatilize the compound A and form a precursor of the skin layer; wherein, the temperature of the air section is 30 °C, the time of the preliminary phase separation is 5 ms, the preliminary phase separation is accompanied by blowing treatment, the blowing speed is 5 m / min, and the blowing gas is argon.

[0127] Step 4: Use the coolant non-solvent compound B (dimethyl phthalate) to carry out cooling phase separation on the molded product after the preliminary phase separation to obtain a green film with a skin layer; wherein, the temperature of the cooling phase separation is 5 °C, and the time of the cooling phase separation is 1.5 s; the temperature of the cooling phase separation is 25 °C lower than the temperature of the air section.

[0128] Among them, in Step 3 and Step 4, the running speed of the molded product is 45 m / min.

[0129] Step 5: Remove the compound A and the compound B from the green film to obtain the original film; wherein, the removal step includes washing and extraction, the temperature of the washing and extraction is 75 °C, the time is 5 h, and the extraction liquid is ethanol.

[0130] Step 6: Dry and shape the original film obtained in Step 5 to obtain an asymmetric PMP hollow fiber oxygenation membrane; wherein, the drying and shaping include heat drying and heat setting; the temperature of the heat drying is 60 °C, and the time is 70 min; the temperature of the heat setting is 150 °C, and the time is 6 s. Among them, the average thickness of the oxygenation membrane is 100 μm.

[0131] Example 3

[0132] Prepare the oxygenation membrane according to the following method:

[0133] Step 1: Heat and plasticize PMP; dissolve it in the weak solvent compound A (diethyl phthalate) and carry out kneading to obtain a homogeneous casting solution; wherein, the solid content of PMP in the casting solution is 35%; the temperature of the kneading is 261 °C, and the pressure of the kneading is 2.5 MPa.

[0134] Step 2: Extrude the casting solution obtained in Step 1 under the die head to form a molded product having an inner surface and an outer surface; wherein, the extrusion temperature is 241°C; the extrusion temperature is 20°C lower than the mixing temperature.

[0135] Step 3: Perform preliminary phase separation on the molded product obtained in Step 2 in the air section to volatilize Compound A to form a precursor of the skin layer;; wherein, the temperature of the air section is 70°C, the time for the preliminary phase separation is 25 ms, the preliminary phase separation is accompanied by a blowing treatment, the blowing speed is 15 m / min, and the blowing gas is helium.

[0136] Step 4: Cool and phase-separate the molded product after the preliminary phase separation with a coolant non-solvent Compound B (dimethyl carbonate) to obtain a green film with a skin layer; wherein, the temperature for the cooling and phase separation is 30°C, the time for the cooling and phase separation is 8 s; the temperature for the cooling and phase separation is 35°C lower than the temperature of the air section.

[0137] Wherein, in Step 3 and Step 4, the running speed of the molded product is 70 m / min.

[0138] Step 5: Remove Compound A and Compound B from the green film to obtain a raw film; wherein, the removal step includes washing and extraction, the temperature for the washing and extraction is 65°C, the time is 7 h, and the extraction liquid is isobutanol.

[0139] Step 6: Dry and shape the raw film obtained in Step 5 to obtain an asymmetric PMP hollow fiber oxygenation membrane; wherein, the drying and shaping includes thermal drying and thermal shaping; the temperature for thermal drying is 45°C, the time is 110 min; the temperature for thermal shaping is 125°C, the time is 18 s. The average thickness of the oxygenation membrane is 80 μm.

[0140] Test Example I

[0141] (1) Structure test

[0142] Perform structure characterization on the oxygenation membranes prepared in Examples 1-3, use a scanning electron microscope (Hitachi S-5500) to perform morphological characterization on the membrane main structure of each example sample, and then obtain the required data; and obtain corresponding data through other tests; the specific results are shown in Tables 1-5.

[0143] Wherein, Figure 2 The schematic diagram of the scanning electron microscope (SEM) of the outer surface of the oxygenation membrane prepared in Example 1 is shown. Figure 3 The schematic diagram of the scanning electron microscope (SEM) of the cross-section of the oxygenation membrane prepared in Example 1 in the direction from the inner surface to the outer surface is shown. Figure 4 and Figure 5The figure shows a scanning electron microscope (SEM) schematic diagram of the oxygenation membrane support layer prepared in Example 1, where Figure 5 is a scanning electron microscope (SEM) schematic diagram of the support layer near the inner surface. Figure 6 and Figure 7 The figure shows a scanning electron microscope (SEM) schematic diagram of the inner surface of the oxygenation membrane prepared in Example 3.

[0144] (2) Performance test - oxygen flux and separation ratio α(CO 2 / O 2 ) test

[0145] The oxygenation membranes prepared in Examples 1-3 were tested for oxygen flux. The specific test method is as follows:

[0146] Under the conditions of a temperature of 25 °C, a pressure of 1 bar, and an oxygenation membrane sample area of 0.1 m 2 , one side of the oxygenation membrane sample was exposed to the gas to be tested (oxygen and carbon dioxide); the gas to be tested was supplied into the inner cavity of the oxygenation membrane sample, and the volumetric flow rate of the gas passing through the membrane wall of the oxygenation membrane sample was measured using a flow meter (KOFLOC / 4800, Japan); it was tested 3 times from inside the membrane to outside the membrane and also 3 times from outside the membrane to inside the membrane, and then the average value was taken. This average value is the gas flux of the oxygenation membrane, and the unit of gas flux is: ml / (cm 2 ×min×bar); among them, the ratio of the gas flux of carbon dioxide to the gas flux of oxygen is the separation ratio α(CO 2 / O 2 ), and the specific results are shown in Table 2.

[0147] Table 1 - Outer surface related characteristics

[0148]

[0149] Table 2 - Overall characteristics of the oxygenation membrane

[0150]

[0151] Table 3 - Cortex related characteristics

[0152]

[0153]

[0154] Table 4 - Support layer related characteristics

[0155]

[0156] Table 5 Inner surface related characteristics

[0157]

[0158] The asymmetric PMP hollow fiber oxygenation membranes prepared in Examples 1-3 all have an ideal pore structure. The outer surface is dense, the overall pore size of the membrane is very small, the bubble point is high, it has a suitable oxygen flux and excellent separation ratio, and the skin layer is thin and uniform. Therefore, it is beneficial for the oxygenation membrane to have oxygenation performance and a long plasma penetration time, and can work efficiently for a long time. It can truly be used as an "artificial lung" to provide arterial blood for human organs and enable human organs to still work normally. It is suitable for various extracorporeal life supports (including cardiac surgery, cardiopulmonary transplantation bridging, emergency cardiopulmonary resuscitation, acute respiratory distress syndrome, cardiopulmonary organ transplantation, multiple organ failure, and congenital heart disease in children).

[0159] Comparative Example 1

[0160] It was carried out with reference to Example 1. The difference is that when preparing the PMP hollow fiber oxygenation membrane, the solid content of PMP in the casting solution in Step 1 was relatively low, only 20%; the other conditions remained unchanged;

[0161] In the finally prepared PMP hollow fiber oxygenation membrane, the outer surface of the oxygenation membrane is not dense, that is, there are a certain number of holes with a certain pore size; this will cause a significant reduction in the oxygenation performance of the oxygenation membrane; at the same time, the tolerance is poor and the plasma penetration time is too short.

[0162] Comparative Example 2

[0163] It was carried out with reference to Example 1. The difference is that in Step 1, after PMP was heated and plasticized, it was dissolved in the strong solvent dioctyl adipate, and not dissolved in the weak solvent Compound A; the other conditions remained unchanged;

[0164] In the finally prepared PMP hollow fiber oxygenation membrane, the pore size of the overall holes of the oxygenation membrane is too large, that is, the initial bubble point of the hydrofluoroether of the oxygenation membrane is lower than 2 MPa; this will cause a significant reduction in the oxygenation performance of the oxygenation membrane.

[0165] Comparative Example 3

[0166] It was carried out with reference to Example 1. The difference is that in Step 1, the solid content of PMP in the casting solution was relatively high, 55%; the other conditions remained unchanged;

[0167] In the finally prepared PMP hollow fiber oxygenation membrane, the overall porosity of the oxygenation membrane is low, and the porosity is only 20%; the oxygenation performance of the oxygenation membrane is too low.

[0168] Comparative Example 4

[0169] It was carried out with reference to Example 1. The difference is that in Step 4, the phase separation temperature during cooling and phase separation was 1 °C and the phase separation time was 0.1 s; the other conditions remained unchanged;

[0170] In the finally obtained PMP hollow fiber oxygenation membrane, the oxygen flux of the oxygenation membrane is too low, and the oxygen flux is only 0.5 ml / (cm 2 ×min×bar), so that oxygen cannot enter the human blood at a relatively fast speed, affecting the oxygenation performance.

[0171] Comparative Example 5

[0172] It was carried out with reference to Example 1. The difference is that in Step 4, the phase separation temperature during cooling phase separation is 50 °C, and the phase separation time is 15 s; other conditions remain unchanged;

[0173] In the finally obtained PMP hollow fiber oxygenation membrane, the oxygen flux of the oxygenation membrane is too large, and the oxygen flux is 3.2 ml / (cm 2 ×min×bar), but the oxygenation performance has not improved, but decreased, and at the same time the plasma penetration time is too low.

[0174] Comparative Example 6

[0175] It was carried out with reference to Example 1. The difference is that when preparing the PMP hollow fiber oxygenation membrane, the preliminary phase separation treatment in Step 3 was not carried out, and the pre-cortex was not formed; other conditions remain unchanged;

[0176] In the finally obtained PMP hollow fiber oxygenation membrane, the separation ratio of the oxygenation membrane is too low, and the separation ratio α (CO 2 / O 2 ) of carbon dioxide to oxygen is only 1.2, and carbon dioxide cannot be quickly and effectively removed from the blood, and the oxygenation performance is greatly affected.

[0177] By comparing Example 1 with Comparative Examples 1-6, it can be seen that the PMP oxygenation membrane of the present invention, through the synergistic effect of regulating that the outer surface of the membrane is dense, the overall pore size of the oxygenation membrane is small (the initial bubble point of hydrofluoroether is not lower than 2 MPa) and the porosity is high (the number of membrane pores is very large), further regulates that the oxygenation membrane has a suitable oxygen flux and an extremely high separation ratio α of carbon dioxide to oxygen. It truly greatly improves the oxygenation ability of the oxygenation membrane (the improvement of oxygenation performance is the result of the combined action of each characteristic of the membrane, and none of them can be missing), shortens the gap with the human lungs, and can truly be used as an "artificial lung" to provide arterial blood for human organs and enable human organs to still work normally.

[0178] Example 4 Group

[0179] This group of examples is used to verify the influence brought about by the change of the "average cortex thickness".

[0180] This group of examples was carried out with reference to Example 1. The difference is that the average cortex thickness is regulated by changing the "solid content of PMP in the casting solution" and the "time of preliminary phase separation", as follows:

[0181] Example 4a. In step 1, the solid content of PMP in the casting solution was set to 46%. In step 3, the initial phase separation time was set to 50 ms. In the finally obtained PMP hollow fiber oxygenation membrane, the average thickness of the skin layer was 1.8 μm.

[0182] Example 4b. In step 1, the solid content of PMP in the casting solution was set to 48%. In step 3, the initial phase separation time was set to 100 ms. In the finally obtained PMP hollow fiber oxygenation membrane, the average thickness of the skin layer was 2.5 μm.

[0183] Example 5 group

[0184] This group of examples was used to verify the influence brought about by the change of "the ratio of the standard deviation of the skin layer thickness to the average thickness of the skin layer".

[0185] This group of examples was carried out with reference to Example 1. The difference was that by changing the "temperature of the air section" and the "blowing speed of the blowing treatment", the ratio of the standard deviation of the skin layer thickness to the average thickness of the skin layer was regulated, as follows:

[0186] Example 5a. In step 3, the temperature of the air section was 73 °C, and the temperature of the cooling phase separation (the temperature of the cooling phase separation remained 22 °C) was 51 °C lower than the temperature of the air section. At the same time, the blowing speed during the blowing treatment was relatively slow, being 3 m / min. In the finally obtained PMP hollow fiber oxygenation membrane, the ratio of the standard deviation of the skin layer thickness to the average thickness of the skin layer was 1.2.

[0187] Example 5b. In step 3, the temperature of the air section was 90 °C, and the temperature of the cooling phase separation (the temperature of the cooling phase separation remained 22 °C) was 68 °C lower than the temperature of the air section. At the same time, no blowing treatment was carried out. In the finally obtained PMP hollow fiber oxygenation membrane, the ratio of the standard deviation of the skin layer thickness to the average thickness of the skin layer was 2.1.

[0188] Example 6 group

[0189] This group of examples was used to verify the influence brought about by the change of "selection coefficient X".

[0190] This group of examples was carried out with reference to Example 1. The difference was that by changing the "solid content of PMP in the casting solution" and the "temperature of the air section" or the "blowing speed of the blowing treatment", the selection coefficient X was regulated, as follows:

[0191] Example 6a. In step 1, the solid content of PMP in the casting solution was set to 34%. In step 3, the temperature of the air section was 65 °C, and the temperature of the cooling phase separation (the temperature of the cooling phase separation remained 22 °C) was 43 °C lower than the temperature of the air section. In the finally obtained PMP hollow fiber oxygenation membrane, the external surface selection coefficient X was 0.38.

[0192] Example 6b: In step 1, the solid content of PMP in the casting solution was set to 30%. In step 3, the temperature of the air section was 82°C, and the temperature of the cooling and phase separation section (the temperature of the cooling and phase separation section remained 22°C) was 60°C lower than that of the air section. In the finally prepared PMP hollow fiber oxygenation membrane, the outer surface selectivity coefficient X was 0.2;

[0193] Example 6c: In step 1, the solid content of PMP in the casting solution was set to 47%, and the blowing speed during the blowing treatment was 5 m / min. In the finally prepared PMP hollow fiber oxygenation membrane, the outer surface selectivity coefficient X was 0.76;

[0194] Example 6d: In step 1, the solid content of PMP in the casting solution was set to 49%, and the blowing speed during the blowing treatment was relatively slow, at 2 m / min. In the finally prepared PMP hollow fiber oxygenation membrane, the outer surface selectivity coefficient X was 0.92.

[0195] Example 7 group

[0196] This group of examples was used to verify the influence brought about by the change of the "crystallization coefficient Y".

[0197] This group of examples was carried out with reference to Example 1. The difference was that the crystallization coefficient Y was regulated by changing the "running speed of the molded product" and the "temperature and time of heat drying" or the "temperature and time of heat setting", specifically as follows:

[0198] Example 7a: In steps 3 and 4, the running speed of the molded product was 40 m / min. In step 6, the drying and setting included heat drying and heat setting, where the temperature of heat drying was 40°C and the time of heat drying was 60 min. In the finally prepared PMP hollow fiber oxygenation membrane, the crystallization coefficient Y on the outer surface was 0.03; the porosity of the oxygenation membrane was 44%;

[0199] Example 7b: In steps 3 and 4, the running speed of the molded product was 20 m / min. In step 6, the drying and setting included heat drying and heat setting, where the temperature of heat drying was 35°C and the time of heat drying was 50 min. In the finally prepared PMP hollow fiber oxygenation membrane, the crystallization coefficient Y on the outer surface was 0.01; the porosity of the oxygenation membrane was 40%;

[0200] Example 7c: In steps 3 and 4, the running speed of the molded product was 80 m / min. In step 6, the drying and setting included heat drying and heat setting, where the temperature of heat setting was 160°C and the time of heat setting was 20 s. In the finally prepared PMP hollow fiber oxygenation membrane, the crystallization coefficient Y on the outer surface was 0.10; the porosity of the oxygenation membrane was 69%;

[0201] In Example 7d, in Steps 3 and 4, the running speed of the molded product is 100 m / min; in Step 6, the drying and shaping include heat drying and heat shaping, where the temperature of heat shaping is 170 °C and the time of heat shaping is 30 s;

[0202] In the finally obtained PMP hollow fiber oxygenation membrane, the crystallization coefficient Y on the outer surface is 0.14; the porosity of the oxygenation membrane is 70%.

[0203] Example 8 group

[0204] This group of examples is used to verify the influence brought by the change of "the ratio Z of the peak area of the fourth peak to the peak area of the third peak".

[0205] This group of examples is carried out with reference to Example 1. The difference is that Z is regulated by changing "the extrusion temperature", "the temperature and time of heat drying" and "the temperature and time of heat shaping", specifically as follows:

[0206] In Example 8a, the kneading temperature in Step 1 is still 242 °C, and the extrusion temperature in Step 2 is set to 217 °C; the extrusion temperature is 25 °C lower than the kneading temperature;

[0207] In Step 6, the drying and shaping include heat drying and heat shaping. The temperature of heat drying is set to 39 °C and the time of heat drying is 55 min; and the temperature of heat shaping is 115 °C and the time of heat shaping is 4 s;

[0208] In the finally obtained PMP hollow fiber oxygenation membrane, the ratio Z of the peak area of the fourth peak to the peak area of the third peak is 1.08.

[0209] In Example 8b, the kneading temperature in Step 1 is still 242 °C, and the extrusion temperature in Step 2 is set to 239 °C; the extrusion temperature is 3 °C lower than the kneading temperature;

[0210] In Step 6, the drying and shaping include heat drying and heat shaping. The temperature of heat drying is set to 61 °C and the time of heat drying is 120 min; and the temperature of heat shaping is 161 °C and the time of heat shaping is 21 s;

[0211] In the finally obtained PMP hollow fiber oxygenation membrane, the ratio Z of the peak area of the fourth peak to the peak area of the third peak is 1.65;

[0212] In Example 8c, the kneading temperature in Step 1 is still 242 °C, and the extrusion temperature in Step 2 is set to 241 °C; the extrusion temperature is 1 °C lower than the kneading temperature;

[0213] The drying and shaping in Step 6 include heat drying and heat setting. The temperature of heat drying is set at 72 °C and the time of heat drying is 140 min; and the temperature of heat setting is 170 °C and the time of heat setting is 32 s;

[0214] In the finally prepared PMP hollow fiber oxygenation membrane, the ratio Z of the peak area of the fourth peak to the peak area of the third peak is 1.97.

[0215] Test Example II

[0216] (1) Tensile strength and elongation at break test

[0217] The asymmetric PMP hollow fiber oxygenation membrane prepared in the examples was used as a specimen for tensile strength and elongation at break tests. The specific test methods are as follows:

[0218] At room temperature (25 °C), each specimen was stretched uniformly with a tensile machine (the stretching speed was 50 mm / min and the distance between the upper and lower clamps was 30 mm) until the specimen broke. Thus, the tensile strength and elongation at break were measured, and the test was repeated 3 times and the average value was taken. The results showed that the tensile strength of all examples of the present invention was not less than 80 cN, and the elongation at break was not less than 80%, indicating that the oxygenation membrane of the present invention has excellent mechanical properties and high industrial practical value.

[0219] (2) Plasma permeation time test

[0220] The asymmetric PMP hollow fiber oxygenation membrane prepared in the examples was used as a specimen for plasma permeation time tests. The specific test methods are as follows:

[0221] Let a phospholipid solution at 37 °C (1.5 g of lecithin dissolved in 500 ml of physiological saline solution) flow through the surface of the specimen at a rate of 6 L / (min×m 2 ) and a pressure of 1.0 bar. Let air flow along the other side of the specimen, and the air flowing through the specimen passes through a cold trap. The weight of the liquid accumulating in the cold trap was measured as a function of time. When a significant increase in weight occurred, that is, the time when the liquid first significantly accumulated in the cold trap was defined as the plasma leakage time, and the results were recorded in Table 6.

[0222] (3) Oxygen saturation test

[0223] The asymmetric PMP hollow fiber oxygenation membranes prepared in the examples and comparative examples were used as specimens for oxygen saturation, oxygen partial pressure, carbon dioxide partial pressure, and end-tidal carbon dioxide concentration tests. The specific test methods are as follows:

[0224] On the basis of the ISO-7199 standard, at 1.6 m 2Under the condition that the blood flow rate for the treatment of the oxygenation membrane sample is 5 L / min, use a blood gas analyzer to measure the oxygen saturation, oxygen partial pressure, and carbon dioxide partial pressure of the blood (arterial blood), and measure the end-tidal carbon dioxide concentration. The schematic diagram of the test device is as shown in Figure 8 shown, and the results are recorded in Table 6.

[0225] Table 6

[0226]

[0227]

[0228] Note: " / " in Table 6 indicates not tested.

[0229] As can be seen from Table 6, compared with the comparative example, the oxygenation membrane of the present invention has excellent oxygenation performance; and the oxygenation membrane of the present invention has a longer plasma permeation time.

[0230] The preferred embodiments of the present invention have been described in detail above. However, the present invention is not limited thereto. Within the scope of the technical concept of the present invention, various simple modifications can be made to the technical solutions of the present invention, including any other suitable combination of each technical feature. These simple modifications and combinations should also be regarded as the content disclosed by the present invention and fall within the protection scope of the present invention.

Claims

1. An asymmetric PMP hollow fiber oxygenation membrane, characterized in that: It comprises a main body, one side of the main body is an inner surface facing the inner cavity, and the other side of the main body is an outer surface; The outer surface has a dense surface; The initial bubbling point of the hydrofluoroether of the oxygenation membrane is not less than 2MPa, and the porosity of the oxygenation membrane is 40%-70%; The oxygen flux of the oxygenation membrane is 1 ml / (cm 2 ×min×bar)-2.5ml / (cm 2 ×min×bar), the separation ratio of carbon dioxide to oxygen α(CO2 / O2) of the oxygenation membrane is not less than 1.

8.

2. The asymmetric PMP hollow fiber oxygenation membrane according to claim 1, characterized in that: The main body comprises a skin layer and a support layer; the side of the skin layer facing away from the support layer is the outer surface, and the side of the support layer facing away from the skin layer is the inner surface; The average thickness of the skin layer is 0.1 μm-3 μm; the ratio of the average thickness of the skin layer to the average thickness of the oxygenation membrane is not greater than 5%; The ratio of the standard deviation of the cortical thickness to the average thickness of the cortical layer is 0.01-1.

5.

3. The asymmetric PMP hollow fiber oxygenation membrane according to claim 1 or 2, characterized in that: The ATR infrared absorption spectrum of the outer surface is 2940 cm -1 -2960cm -1 There is a first peak at 1455cm -1 -1475cm -1 There is a second peak; The ratio of the peak area of ​​the first peak to the peak area of ​​the second peak is the selectivity coefficient X, and the selectivity coefficient X is 0.3-0.85; preferably 0.45-0.7; The average thickness of the skin layer is 0.3 μm-2 μm, preferably 0.4 μm-1.5 μm.

4. The asymmetric PMP hollow fiber oxygenation membrane according to claim 1 or 2, characterized in that: The ATR infrared absorption spectrum of the outer surface is 910 cm -1 -930cm -1 There is a third peak at 1455cm -1 -1475cm -1 There is a second peak; The ratio of the peak area of ​​the third peak to the peak area of ​​the second peak is the crystallization coefficient Y, and the crystallization coefficient Y is 0.02-0.12; preferably 0.04-0.08; The ratio of the average thickness of the skin layer to the average thickness of the oxygenation membrane is 0.2%-4%, and the porosity of the oxygenation membrane is 45%-68%.

5. The asymmetric PMP hollow fiber oxygenation membrane according to claim 1 or 2, characterized in that: The ATR infrared absorption spectrum of the outer surface is 910 cm -1 -930cm -1 There is a third peak; the ATR infrared absorption spectrum of the inner surface is at 910cm -1 -930cm -1 There is a fourth peak; Preferably, the ratio Z of the peak area of ​​the fourth peak to the peak area of ​​the third peak is 1.05-1.8; more preferably 1.1-1.55; The separation ratio α (CO2 / O2) of carbon dioxide to oxygen of the oxygenation membrane is 2.1-3.

6. The asymmetric PMP hollow fiber oxygenation membrane according to claim 1 or 2, characterized in that: The DSC crystallinity of the oxygenated film is 30%-60%; the average thickness of the oxygenated film is 70 μm-120 μm.

7. The asymmetric PMP hollow fiber oxygenation membrane according to claim 2, characterized in that: The support layer has support fibers for forming a porous structure, and the SEM average width of the support fibers is 40nm-150nm; The cross section of the support layer along the inner surface toward the outer surface is a first cross section, the first cross section has a first hole, and the ratio of the SEM average pore size of the first hole to the SEM average width of the support fiber is (1.5-5):

1.

8. The asymmetric PMP hollow fiber oxygenation membrane according to claim 7, characterized in that: The average pore size of the first pores by SEM is 0.12 μm-0.45 μm, and the pore density of the first pores is 30 / 25 μm. 2 -180 pieces / 25μm 2 .

9. The asymmetric PMP hollow fiber oxygenation membrane according to claim 7, characterized in that: The inner surface is provided with a plurality of air holes; the SEM average pore size of the air holes is 0.15 μm-0.8 μm, and the hole area rate of the air holes on the inner surface is 5%-25%; And / or, the ratio of the SEM average pore size of the air pores to the SEM average pore size of the first holes is (1.2-3):

1.

10. The asymmetric PMP hollow fiber oxygenation membrane according to claim 2, characterized in that: The inner surface is provided with a plurality of surface fibers for supporting the air pores, the SEM average width of the surface fibers is 60nm-250nm, and the ratio of the SEM average width of the surface fibers to the SEM average pore size of the air pores is not less than 0.

1.

11. The asymmetric PMP hollow fiber oxygenation membrane according to claim 1 or 2, characterized in that: The oxygenation membrane also meets one or more of the following characteristics: (1) The tensile strength of the oxygenated membrane is not less than 80 cN, and the elongation at break is not less than 80%; (2) The plasma permeation time of the oxygenation membrane is not less than 48 hours, preferably not less than 96 hours; (3) At 1.6m 2 When the oxygenation membrane processes blood at a flow rate of 5 L / min, the oxygen saturation of arterial blood is not less than 99%, the oxygen partial pressure is not less than 150 mmHg, the carbon dioxide partial pressure is not higher than 46 mmHg; and the end-tidal carbon dioxide concentration is not less than 29 mmHg.

12. A method for preparing an asymmetric PMP hollow fiber oxygenation membrane according to any one of claims 1 to 11, characterized in that: The preparation method comprises the following steps: Step 1: heat and plasticize PMP; dissolve it in weak solvent compound A and mix it to obtain a homogeneous casting solution; the solid content of PMP in the casting solution is 30%-49%; The compound A comprises at least one of N,N-bis-2-hydroxyethyl hexadecylamine, methyl-12-hydroxystearic acid, paraffin oil, dibutyl sebacate, dibutyl phthalate, diethyl phthalate and oleamide; Step 2: Extruding the casting liquid under a die head to form a molded product having an inner surface and an outer surface; Step 3: performing preliminary phase separation on the molded product in an air section, wherein compound A volatilizes to form a skin precursor; Step 4: Cooling and separating the molded product after the preliminary phase separation with a coolant compound B to obtain a raw film with a skin layer; wherein the temperature of the cooling phase separation is 3°C-40°C, and the time of the cooling phase separation is 0.5s-10s; the compound B includes at least one of polyethylene glycol 400, glycerol, pure water, peanut oil, diacetin, dimethyl phthalate, dimethyl carbonate and triacetin; Step 5: removing the compound A and the compound B from the raw film to obtain an original film; Step 6: Drying and shaping the original membrane to obtain the asymmetric PMP hollow fiber oxygenation membrane.

13. The preparation method according to claim 12, characterized in that: In step three, the temperature of the air section is 10°C-80°C, and the time of the preliminary phase separation is 1ms-30ms; the preliminary phase separation is accompanied by blowing treatment, the blowing speed is 5m / min-20m / min, and the blowing gas is at least one of nitrogen, argon and helium.

14. The preparation method according to claim 12, characterized in that: The mixing temperature in step 1 is 210°C-270°C, and the extrusion temperature in step 2 is 220°C-250°C; And / or, in step 3 and step 4, the running speed of the molded product is 40m / min-80m / min; And / or, the temperature of the cooling phase is 10° C. to 50° C. lower than the temperature of the air section.

15. The preparation method according to claim 12, characterized in that: The removal step in step 5 includes washing and extraction, the washing and extraction temperature is 60°C-80°C, and the washing and extraction time is 4h-8h; the washing and extraction uses an extraction liquid, and the extraction liquid includes at least one of isopropanol, ethanol, isobutanol and acetone; And / or, the extrusion temperature is 5°C-25°C lower than the mixing temperature.

16. The preparation method according to claim 12, characterized in that: The drying and shaping in step 6 includes heat drying and heat shaping; The heat drying temperature is 40°C-60°C, and the heat drying time is 60min-120min; And / or, the heat setting temperature is 120° C.-160° C., and the heat setting time is 5s-20s.

17. An application of an asymmetric PMP hollow fiber oxygenation membrane, characterized in that: The asymmetric PMP hollow fiber oxygenation membrane is used for extracorporeal membrane oxygenation and / or extracorporeal carbon dioxide removal, and the asymmetric PMP hollow fiber oxygenation membrane comprises the asymmetric PMP hollow fiber oxygenation membrane described in any one of claims 1-11 or the asymmetric PMP hollow fiber oxygenation membrane prepared by the preparation method described in any one of claims 12-16.

Citation Information

Cited By

  • High-strength double-layer hollow fiber membrane and preparation method thereof

    CN120960997A